Von Economo neurons are part of a larger neuronal population that are selectively vulnerable in C9orf72 frontotemporal dementia. (10th June 2019) - Gami‐Patel, P.; van Dijken, I.; van Swieten, J. C.; Pijnenburg, Y. A. L.; ,; Rozemuller, A. J. M.; Hoozemans, J. J. M.; Dijkstra, A. A.
Abstract : Aims: The behavioural variant of frontotemporal dementia with a C9orf72 expansion (C9‐bvFTD) is characterised by early changes in social‐emotional cognition that are linked to the loss of von Economo neurons (VENs). Together with a subset of neighbouring pyramidal neurons, VENs express the GABA receptor subunit theta (GABRQ). It is not known if the selective vulnerability of VENs in C9‐bvFTD also includes this GABRQ‐expressing population. Methods: We quantified VENs and GABRQ immunopositive neurons in the anterior cingulate cortex (ACC) in C9‐bvFTD ( n  = 16), controls ( n  = 12) and Alzheimer's disease (AD) ( n  = 7). Second, we assessed VENs and GABRQ‐expressing populations in relation to the clinicopathological profiles. Results: We found the number of VENs and GABRQ‐expressing neurons and their ratio over the total layer 5 neuronal population was lower in C9‐bvFTD compared to control and AD. C9‐bvFTD donors with underlying TDP43 type A pathology in the ACC showed the highest loss of GABRQ‐expressing neurons. C9‐bvFTD donors that did not present with motor neuron disease (MND) symptoms in the first half of their disease course showed a prominent loss of GABRQ‐expressing neurons compared to controls. C9‐bvFTD donors with no symptoms of psychosis showed a higher loss compared to controls. Across all donors, the number of VENs correlated strongly with the number of GABRQ‐expressing neurons. Conclusion: We show that VENs, together with GABRQ‐expressing neurons, are selectively vulnerable in C9‐bvFTD but are both spared in AD. This suggests they are related and that this GABRQ‐expressing population of VENs and pyramidal neurons, is a key modulator of social‐emotional functioning.